2013
DOI: 10.1038/cddis.2013.66
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of a Chinese herbal medicine in atherosclerosis via estrogen receptor β mediating nitric oxide production and NF-κB suppression in endothelial cells

Abstract: Bu-Shen-Ning-Xin Decoction (BSNXD) administration has alleviated the early pathologic damage of atherosclerosis by inhibiting the adhesion molecule expression and upregulating the estrogen receptor (ER) β expression in endothelial cells, and increasing the serum nitric oxide (NO) level without any effect on serum lipid status, endometrium and fat deposition in liver in ovariectomized rabbits. The BSNXD-derived serum increases ER β expression in the human umbilical vein endothelial cells (HUVECs), and decreases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 53 publications
0
31
0
Order By: Relevance
“…Levels of DHEA peak during the third decade of life and then decline with age (66). A previous study by the current authors found that BSNXD up-regulated ER rather than E2 in OVX rabbits (6). BSNXD pharmacological serum and DHEA affect osteoblasts via the MAPK pathway (11,67).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Levels of DHEA peak during the third decade of life and then decline with age (66). A previous study by the current authors found that BSNXD up-regulated ER rather than E2 in OVX rabbits (6). BSNXD pharmacological serum and DHEA affect osteoblasts via the MAPK pathway (11,67).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that BSNXD up-regulated serum levels of the estrogen receptor (ER) without affecting E2 in OVX rabbits (6). Hence, a question was whether BSNXD prevented osteoporosis by affecting the production/metabolism of ER ligands, such as DHEA, DHEAS, and E2, in mice.…”
Section: Administration Of Bsnxd Increased Serum Dhea But Not E2mentioning
confidence: 99%
See 1 more Smart Citation
“…NO can react with reactive oxygen species (ROS) to form peroxynitrite that may lead to nitrosylation or nitration on tyrosine residues of proteins (52,53) and thus alter the activities of these proteins. The small quantity of NO generated through eNOS has a protective effect in atherosclerotic lesions (54). Conversely, the inflammatory environment in human atherosclerotic lesion results in The relative expression level of MMP-9 activity.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of well curated databases of ingredients of traditional Chinese medicines has opened up new avenues for molecular screening as well as in-silico studies, including target-based docking (Chen et al, 2006; Fang et al, 2008; Chen, 2011; Zhou, Xie & Yan, 2011). In depth screens of Chinese medicine derived compounds have been performed for a variety of pathophysiologies, including cancer (Hu et al, 2013), inflammatory diseases (Han & Guo, 2012; Su & Hsieh, 2011), cardiovascular diseases (Wang et al, 2013) and infections (Jiang, Deng & Wu, 2013), just to name a few. These databases are being extensively used for therapeutic development (Cheng et al, 2010).…”
Section: Discussionmentioning
confidence: 99%